2020
DOI: 10.2147/dddt.s219247
|View full text |Cite
|
Sign up to set email alerts
|

<p>Aloin Inhibits the Proliferation and Migration of Gastric Cancer Cells by Regulating NOX2–ROS-Mediated Pro-Survival Signal Pathways</p>

Abstract: Background: Aloin has been reported to have many pharmacological effects including antiinflammatory, anti-oxidant and anti-tumour activities. However, the precise molecular mechanisms underlying the anti-tumour properties of aloin are yet to be elucidated. Methods: HGC-27 and BGC-823 gastric cancer cells were treated with aloin. EdU and colony formation assays were used to detect the proliferation ability of cells. The migration of cells was detected using wound healing and transwell assays. Western blotting w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…Western blotting was performed according to the methods described previously by Wang et al 15 . Total protein was extracted from cells using radioimmunoprecipitation assay buffer (Beyotime Institute of Biotechnology, Haimen, China) supplemented with phenylmethylsulfonyl fluoride (PMSF).…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting was performed according to the methods described previously by Wang et al 15 . Total protein was extracted from cells using radioimmunoprecipitation assay buffer (Beyotime Institute of Biotechnology, Haimen, China) supplemented with phenylmethylsulfonyl fluoride (PMSF).…”
Section: Methodsmentioning
confidence: 99%
“…Surprisingly, A922500 treatment also inhibited expression of NOX2 and indoleamine 2,3-dioxygenase (IDO) in MKN45 (Fig. 4 d, e), two genes correlated with proliferation and migration of gastric tumor cells [ 15 , 16 ]. Collectively, oleate sodium elevated DGAT1 expression in gastric cancer cell line MKN45 and DGAT1 blockade induced cell apoptosis in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…Data from several studies suggest that suppressed DGAT1 is a promising strategy to inhibit prostate cancer cell growth and, therefore, targeting DGAT1 might be conducive for clinical gastric cancer treatment [ 12 , 13 ]. It has been previously reported that the elevated level of reactive oxygen species is facilitated to cancer progression and metastasis, and gastric cancer cell proliferation and migration could be suppressed after administration of inhibitor to block the reactive oxygen species production [ 14 16 ]. Another study demonstrated that accumulation of the nicotinamide adenine dinucleotide phosphate oxidase 2 (NOX2) activates Akt, Stat3, and IκBα signaling pathways in two gastric cancer cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NADPH oxidases contain different subtypes, which are well known to be involved in signal transduction associated with inflammation and oxidative stress [27,28]. In these subtypes, NOX2 abundantly expressing in monocytes is currently accepted as the main source of ROS [29,30]. PKC activation also has been identified to play an important part in inflammation and oxidative stress [31,32].…”
Section: Discussionmentioning
confidence: 99%